TRIAGEM FITOQUÍMICA, TOXICIDADE E AVALIAÇÃO DA ATIVIDADE LARVICIDA DE Cedrela fissilis VELL. (MELIACEAE) - PEREIRA, Vanessa Cristina; ALIENDES, Silvia Helena Mittelstett; OLIVEIRA, Melonny Lorraynny Martins; SANTOS, Alexandre Brito; SILVA, Ana Francisca Gomes (ANAIS DO ENIC, 2025)
.